Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1479-5876-9-96
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis of apoptotic hematopoietic stem cells from hemoglobin E/β-thalassemia

Abstract: BackgroundHemoglobin E/β-thalassemia is particularly common in Southeast Asia and has variable symptoms ranging from mild to severe anemia. Previous investigations demonstrated the remarkable symptoms of β-thalassemia in terms of the acceleration of apoptotic cell death. Ineffective erythropoiesis has been studied in human hematopoietic stem cells, however the distinct apoptotic mechanism was unclear.MethodsThe phosphoproteome of bone marrow HSCs/CD34+ cells from HbE/β-thalassemic patients was analyzed using I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 58 publications
(63 reference statements)
0
26
1
Order By: Relevance
“…Moreover, the apoptotic effector protein, activated Caspase 3, was also significantly expressed in a synthetic erythropoiesis model of b-thalassemia derived by knocking down b-globin gene of normal CD34 1 cells [65]. The supporting evidence by phosphoproteomic analysis from hemoglobin E/b-thalassemia CD34 1 cells showed the various apoptosis-related protein upregulations including apoptosis-inducing factor, mitochondria associated 1 (AIFM1) [66]. Therefore, in this study we demonstrated that the apoptosis related-genes, CASP3 (caspase 3) and AFFM1, were highly expressed in patient erythroblasts and decreased in the corrected cells suggesting that the apoptosis cascade process might be less active as a consequential result of the partial restoration of correctly spliced b-globin mRNA.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the apoptotic effector protein, activated Caspase 3, was also significantly expressed in a synthetic erythropoiesis model of b-thalassemia derived by knocking down b-globin gene of normal CD34 1 cells [65]. The supporting evidence by phosphoproteomic analysis from hemoglobin E/b-thalassemia CD34 1 cells showed the various apoptosis-related protein upregulations including apoptosis-inducing factor, mitochondria associated 1 (AIFM1) [66]. Therefore, in this study we demonstrated that the apoptosis related-genes, CASP3 (caspase 3) and AFFM1, were highly expressed in patient erythroblasts and decreased in the corrected cells suggesting that the apoptosis cascade process might be less active as a consequential result of the partial restoration of correctly spliced b-globin mRNA.…”
Section: Discussionmentioning
confidence: 88%
“…A total of seven studies have investigated differential protein expression in a range of patient specimens (Table ). Most of the studies have investigated differences between normal controls and β‐thalassemia/Hb E patients [, ], while in one study four cohorts (Normal control, β‐thalassemia/Hb E non‐splenectomized, β‐thalassemia/Hb E splenectomized and β‐thalassemia) were investigated .…”
Section: Studiesmentioning
confidence: 99%
“…additionally compared between mild and severe forms of β‐thalassemia/Hb E . The studies variously analyzed platelets , erythrocytes , platelet‐free plasma derived microparticles , plasma , erythroid progenitor cells and bone marrow derived CD34+ cells . The predominant separation methodology employed was two‐dimensional gel electrophoresis (2‐DE; ) which was used by five studies , although one study additionally employed two‐dimensional difference in gel electrophoresis (2D‐DIGE), a technique solely employed by Weeraphan et al.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ineffective erythropoiesis in human hematopoietic stem cells has been implicated in Hemoglobin E/beta-thalassemia. Ponnikorn et al compared the phosphoprofiling of human hematopoietic cells between healthy donors and Hemoglobin E/beta-thalassemia patients (Ponnikorn et al, 2011). They enriched the phoshoproteins by IMAC, followed by LC-MS/MS for identification, and found 229 differentially phosphorylated proteins.…”
Section: Quantification Of Protein Phosphorylationmentioning
confidence: 99%